Kebijakan Pengambilan Keputusan Pimpinan Dilingkungan Pondok Pesantren untuk Meningkatkan Kualitas Manajerial Pendidikan Formal - Aslamiyah, Nurul; Supriyanto, Aris; Harahap, Nasrudin; Murtafiah, Nurul Hidayati (CV. Creative Tugu Pena, 2022)
The purpose of this study is to analyze the decision-making used by leaders in Pondok Pesantren, also known as pesantren, because of their substantial impact on official educational institutions. To achieve its goals, various organizations that oversee Islamic boarding schools use various methodologies and standards for decision making. Design, implementation, and assessment of decision making are the main topics of this research. The method known as descriptive qualitative is applied in this study. Interviews, documentation, and observations were used to collect data. Data reduction, data presentation, and data verification are data analysis methods used. In this study, the aim is to determine the design in decision making, to determine the decision-making process and to determine the assessment criteria used by the leadership. The results show that: first, design decision-making involves processes such as team building, needs analysis, program design, program socialization, and process assessment; second, the purpose of design decision-making is to improve the quality of management. Second, the use of the decision-making process by leaders can be observed in the improvement of human resources, where they focus and highlight this particular issue as it is closely related to school administration standards. Third, the leader's performance is assessed either directly or indirectly through conversation. The assessment criteria used are procedures through which choices are evaluated, along with the consequences of the decisions, to determine their significance Keywords: Leaders' Decision Policy, Managerial Quality Education, Quality Education